Ammonia emission from rice leaves in relation to photorespiration and genotypic differences in glutamine synthetase activity - Kumagai, Etsushi (Oxford University Press, 2011)
BACKGROUND AND AIMS: Rice (Oryza sativa) plants lose significant amounts of volatile NH(3) from their leaves, but it has not been shown that this is a consequence of photorespiration. Involvement of photorespiration in NH(3) emission and the role of glutamine synthetase (GS) on NH(3) recycling were investigated using two rice cultivars with different GS activities. METHODS: NH(3) emission (AER), and gross photosynthesis (P(G)), transpiration (Tr) and stomatal conductance (g(S)) were measured on leaves of ‘Akenohoshi’, a cultivar with high GS activity, and ‘Kasalath’, a cultivar with low GS activity, under different light intensities (200, 500 and 1000 µmol m(−2) s(−1)), leaf temperatures (27·5, 32·5 and 37·5 °C) and atmospheric O(2) concentrations ([O(2)]: 2, 21 and 40 %, corresponding to 20, 210 and 400 mmol mol(−1)). KEY RESULTS: An increase in [O(2)] increased AER in the two cultivars, accompanied by a decrease in P(G) due to enhanced photorespiration, but did not greatly influence Tr and g(S). There were significant positive correlations between AER and photorespiration in both cultivars. Increasing light intensity increased AER, P(G), Tr and g(S) in both cultivars, whereas increasing leaf temperature increased AER and Tr but slightly decreased P(G) and g(S). ‘Kasalath’ (low GS activity) showed higher AER than ‘Akenohoshi’ (high GS activity) at high light intensity, leaf temperature and [O(2)]. CONCLUSIONS: Our results demonstrate that photorespiration is strongly involved in NH(3) emission by rice leaves and suggest that differences in AER between cultivars result from their different GS activities, which would result in different capacities for reassimilation of photorespiratory NH(3). The results also suggest that NH(3) emission in rice leaves is not directly controlled by transpiration and stomatal conductance.